Epidemiology of Joint Dislocations and Ligamentous/Tendinous Injuries among 2,700 Patients: Five-year Trend of a Tertiary Center in Iran - Nabian, Mohammad H. (Arch Bone Jt Surg, 2017)
BACKGROUND: The epidemiology of traumatic dislocations and ligamentous/tendinous injuries is poorly understood. In this study, we aimed to evaluate the prevalence and distribution of various dislocations and ligamentous/tendinous injuries in a tertiary orthopedic hospital in Iran. METHODS: Musculoskeletal injuries in an academic tertiary health care center in Tehran February 2005 to October 2010 were recorded. The demographic details of patients with pure dislocations and ligamentous/tendinous injuries were extracted and the type and site of injuries were classified according to their specific age/gender groups. RESULTS: Among 18,890 admitted patients, 628 (3.3%) were diagnosed with dislocations and 2.081 (11%) with ligamentous/tendinous injuries. The total male/female ratio was 4.2:1 in patients with dislocations and 1.7:1 in patients with ligamentous/tendinous injuries. Shoulder was the most prevalent site of dislocation (50.6%), followed by fingers (10.1%), toes (7.6%), hip (7.3%), and elbow (6.5%). Ankle was the most common site of ligamentous/tendinous injury (53.5%), followed by midfoot (12.3%), knee (8.3%), hand (7%), and shoulder (5%). The mean ages of the patients in dislocations and ligamentous/tendinous injuries were 35.0±18.2 and 31.3± 15.1, respectively. There was no seasonal variation. CONCLUSION: Shoulder dislocation and ankle ligamentous injury are the most frequent injuries especially in younger population and have different distribution patterns in specific age and sex groups. Epidemiologic studies can help develop and evaluate the injury prevention strategies, resource allocation, and training priorities.